Migrations, sexualities and transnational imaginaries: Peruvian women in Buenos Aires and mexican men in Chicago - Rosas, Carolina Alejandra (2019)
This article analyzes imaginaries and rumors about the sexual life of migrants that circulate in transnational communities, through a qualitative approach on Mexican men in Chicago (United States) and Peruvian women in Buenos Aires (Argentina). The findings suggest that in contemporary Latin American mobilities, transnational imaginaries and rumors are the product of tensions between social transformation and control. They express concerns about the possibility of transgressing the limits imposed by the heteropatriarchal organization of sexuality and gender, and by racial constructs and class structure.